2011
DOI: 10.1128/aac.01181-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bacterial NAD + -Dependent DNA Ligase Inhibitors with Broad-Spectrum Activity and Antibacterial Efficacy In Vivo

Abstract: DNA ligases join adjacent 3Ј-hydroxyl and 5Ј-phosphoryl termini to form a phosphodiester bond in duplex DNA (22,38). DNA ligases function in DNA replication, by joining Okazaki fragments on the lagging strand of DNA, and are involved in several DNA repair pathways (e.g., nucleotide excision repair). DNA ligation proceeds in three nucleotidyl transfer steps. The first step involves the formation of a covalent DNA ligase-adenylate intermediate. In the second step, AMP is transferred from DNA ligase to the 5Ј pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 36 publications
0
100
0
Order By: Relevance
“…aureus (MIC 32-64 mg l 21 ). The antibacterial activity of several 2-substituted adenosine analogues has recently been reported by Mills et al (2011). This study showed that 2-thio-n-butyl adenosine was an inhibitor of the bacterial NAD + -dependent DNA ligase.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…aureus (MIC 32-64 mg l 21 ). The antibacterial activity of several 2-substituted adenosine analogues has recently been reported by Mills et al (2011). This study showed that 2-thio-n-butyl adenosine was an inhibitor of the bacterial NAD + -dependent DNA ligase.…”
Section: Resultsmentioning
confidence: 78%
“…Some recent experiences, however, have proven the great value of this field of research. For example, complex nucleosides exhibit antibacterial activity by specific inhibition of cell-wall peptidoglycan biosynthesis (Kimura & Bugg, 2003), certain bacterial enzymes, such as purine nucleoside phosphorylases (Bzowska et al, 2000), and DNA ligases (Mills et al, 2011). In particular, adenosine analogues such as cordycepin (Ahn et al, 2000), 29-amino-29-deoxyadenosine and oxetanocin (Shimada et al, 1986), formycins (Bzowska et al, 2000), toyocamycin and its derivatives (Kimura & Bugg, 2003) and some purine derivatives (Tunçbilek et al, 2009) showed biological activity including antibiotic properties.…”
Section: Introductionmentioning
confidence: 99%
“…the assay has been used for high-throughput screening for the discovery of bacterial NAD + -dependent DNA ligase inhibitors. 5 this article describes in greater detail the development and principle of the assay and illustrates its use for measuring the steady-state kinetic constants of Haemophilus influenzae NAD + -dependent DNA ligase and of inhibitor potency.…”
mentioning
confidence: 99%
“…HY-18649A; Medchemexpress LLC, Princeton, NJ, USA), used as a control] was measured at 10 different compound concentrations in the reaction system in order to determine the 50% inhibitory concentration (IC 50 ). Assays for the other bacterial LigA isozymes were performed as described above for H. influenzae LigA, with the following changes in order to optimize enzyme performance, as previously described (22,23 …”
Section: Methodsmentioning
confidence: 99%